Strategic Litigation in EU Law: Who does it Empower? - Pola Cebulak; Marta Morvillo; Stefan Salomon (German Law Journal)
Strategic litigation is a form of legal mobilization, where actors bring cases before judges not only to win in court, but also to pursue broader political, social or economic ends. Various actors can use the law strategically – big corporations, specialized non-governmental organizations or individual academics. The ends can range from resisting market regulation or a political advocacy campaign to simply “testing the law”. The results of strategic litigation maintain or change power relations in society, economy or politics.